Legal withholding in execution of a judgment: Is res judicata contravened? - Núñez Paz, Sandro (2021)
In this research we will address the controversy that arises when a judicial authority orders in execution of a judgment the execution of obligations to pay a sum of money with respect to labor concepts, after which the companies —as withholding agents— proceed to withhold the amounts corresponding to the payment of income tax and social security concepts; even when this has not been the subject of the judicial pronouncement or the claim discussed in the trial. Thus, there is controversy as to whether this procedure of the companies is correct or whether it contravenes the principle of res judicata.